Evolution of virtual water metabolic network in developing regions: A case study of Guangdong province. (January 2020) - He, Chengyu; Huang, Guohe; Liu, Lirong; Xu, Xinli; Li, Yongping
Highlights: A Virtual Water Metabolic Network (VWMN) is developed from the standpoint of Ecological Network. Self-pulling and self-driving effects are considered in ecological hierarchy analysis. Two indicators are proposed to dig more imformation hidden in VWMN A case study of Guangdong province, China is conducted to show the potential benefits. Abstract: Rapid urbanization has challenged the utilization and the circulation of water, especially in rapidly developing regions. It is necessary to disaggregate virtual water metabolic networks (VWMN) in representative areas, and examine their relevant dynamics to sustain regional development. In this study, the VWMN of Guangdong Province, China is developed to explore the ecological relationships between pairwise components and identify the ecological hierarchy structure of VWMN. Particularly, the structural analysis of VWMN is optimized and two indicators are proposed in this study. The integral virtual water recycling index (IVWRI) enable to reveal the extent that components are benefited from the existence of the VWEN and the integral virtual water productivity (IVWP) can identify economic output per unit integral virtual water utilization of each component. The results indicate that the tertiary industry fails to promote the development of its upstream industries, and the integral virtual water productivity of this industry is declining. Technology upgrading of manufacturing industry and steady import of primary products are imperative. Moreover, petroleum, coking, nuclear-fuel and construction industries are key components that clog the studied VWMN. This research provides scientific support for the robust development of VWMN, particularly in alleviating water scarcity and promoting sustainable regional development.